2019
DOI: 10.3390/nu11020333
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Schisandra chinensis (Turcz.) Baill. in Human Health and Nutrition: A Review of Current Knowledge and Therapeutic Perspectives

Abstract: Schisandra chinensis (Turcz.) Baill. (SCE) is a plant with high potential for beneficial health effects, confirmed by molecular studies. Its constituents exert anti-cancer effects through the induction of cell cycle arrest and apoptosis, as well as inhibition of invasion and metastasis in cancer cell lines and experimental animals. SCE displays antimicrobial effects against several pathogenic strains. It has anti-diabetic potential, supported by hypoglycemic activity. A diet rich in SCE improves pancreatic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 119 publications
0
69
0
3
Order By: Relevance
“…In the present study, we analyzed the beneficial effects of SCE and AA on mitochondrial respiration and behavior. SCE is enriched for a number of bioactive ingredients, including gomisin and schisandrin, as confirmed by HPLC ( Figure S1), and is known to enhance cognitive performance and provide neuroprotection [10,13,29]. AA is present in various plants and is used as a dietary supplement.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In the present study, we analyzed the beneficial effects of SCE and AA on mitochondrial respiration and behavior. SCE is enriched for a number of bioactive ingredients, including gomisin and schisandrin, as confirmed by HPLC ( Figure S1), and is known to enhance cognitive performance and provide neuroprotection [10,13,29]. AA is present in various plants and is used as a dietary supplement.…”
Section: Discussionmentioning
confidence: 86%
“…Schisandra chinensis extract (SCE) has been reported to exert neuroprotective effects [10], including amelioration of cognitive deficits in a mouse model of chronic, unpredictable mild stress [11], and improvement of synaptic morphology and plasticity in ovariectomized mice [12]; it also protects against oxidative stress in hepatocytes [13]. Supplementation with ascorbic acid (AA), a water-soluble vitamin C found in plants, has been reported to prevent impairment of synaptic plasticity and hippocampal LTP attributable to oxidative damage induced by lead, a neurotoxic metal [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schisandra chinensis Baill (Botanical family name: Schisandraceae), called “omija” which means five‐flavored fruit in Korea, is a pharmacological plant mainly grown in Korea, China, Japan, and Russia 3 . Omija ( S chinensis ) fruit has been used as a medicinal plant for liver damage in China over several centuries 3‐5 . In Korea, it is consumed not only as a medicine but also as tea or alcoholic beverages.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, it is consumed not only as a medicine but also as tea or alcoholic beverages. A previous study has reported that S chinensis fruit has the antioxidative activity 3,5 . Lignan compounds, such as schizandrin, gomisin A, and gomisin N, have been identified as the major component which exhibit antioxidative activity 6 .…”
Section: Introductionmentioning
confidence: 99%